Gender differences in the effects of self-congruity on tourist happiness and revisit intentions in ecotourism areas - Kumenaung, Dean Salomo Anthonino; Hendryadi, Hendryadi; Faruqi, Faris; Effendi, Syahrul (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
The research investigated the relationship between self-congruity, perceived happiness, and the intention to revisit an ecotourism destination, mainly focusing on Generation Z in Jakarta. A total of 246 participants were analyzed using multi-group structural equation modeling (SEM). The findings revealed a strong positive correlation between self-congruity and happiness and between self-congruity and the intention to revisit. Additionally, happiness was found to influence the intention to revisit positively. The study also examined how gender differences affect the relationships among self-congruity, happiness, and the intention to revisit. This research provides insights into the connections between self-congruity, happiness, and the desire to return to ecotourism sites, especially among Gen Z travelers. Furthermore, exploring gender differences enhances our understanding of the factors that shape travel behavior and intentions in the context of ecotourism.